Expression of α5-integrin, α7-integrin, Ε-cadherin, and N-cadherin in localized prostate cancer - Drivalos, A.; Chrisofos, M.; Efstathiou, E.; Kapranou, A; Kollaitis, G.; Koutlis, G.; Antoniou, N.; Karanastasis, D.; Dimopoulos, M.A.; Bamias, A. (Urologic Oncology: Seminars and Original Investigations, 2016)
Objective: To explore the correlation between the expression of α5-integrin, α7-integrin, Ε-cadherin, and N-cadherin in prostate cancer (PCa) and its clinicopathological data including tumor grade and clinical stage. Methods: The expression of α5-integrin, α7-integrin, Ε-cadherin, and N-cadherin was examined in 157 cases of PCa and adjacent normal prostatic tissue by immunohistochemical assay, and the correlation with clinicopathological features was analyzed. Results: Expressions of α5-integrin, α7-integrin, and Ε-cadherin in PCa were lower than those in normal prostatic tissues (P<0.05). N-cadherin expression was higher in cancer prostatic tissue than in normal prostatic tissues (P<0.05). The reduced expression of α5-integrin, α7-integrin, and Ε-cadherin was related to Gleason score, pathological stage, lymph node metastasis, and prostate-specific antigen level, but it was not associated with positive surgical margins and patient age. The increased expression of N-cadherin was related to Gleason score, pathological stage, lymph node metastasis, and prostate-specific antigen level, but not to age and positive surgical margins. The expression of E-cadherin was highly negatively correlated with that of N-cadherin and also positively correlated with that of α5-integrin and α7-integrin. Conclusion: The reduced expression of α5-integrin, α7-integrin, and Ε-cadherin and abnormal expression of N-cadherin play an important role in the occurrence and development of PCa. The results indicate that these have potential values in the diagnosis and are predictable indices in the proliferation of PCa. © 2016 Elsevier Inc.
Keywords: Cadherins; Cell adhesion molecules; Integrins; Prostate cancer